Data visualization on student stress level / Nur Syifa Ramzi, Mohammad Hafiz Ismail and Tajul Rosli Razak - Ramzi, Nur Syifa; Ismail, Mohammad Hafiz; Razak, Tajul Rosli (College of Computing, Informatics and Media, UiTM Perlis, 2023)
Stress has become part of students’ academic life due to the various internal and external expectations placed upon their shoulder. Therefore, this research is to visualize on student stress level among universities students. The objective of this project is to analyze the retrieved data on the level that affects students' stress, to visualize the stress levels among university students relate to their issues and to evaluate the proposed visualization dashboard on student stress level using User Acceptance Test (UAT). The method used in the visualization is Microsoft Power BI which allows user to search for data, convert, visualize, and share the dashboards that user create to public. Secondary data from Figshare website was selected to obtain a dataset to be studied using a Power BI. This research will also help individuals build strong interpersonal relationships and deal with stress in their everyday lives by using visual representations of statistical data analysis, thereby making it easier and available to everyone.